Optical Properties Of Surfaces. - Bedeaux, Dick, 1941- (World Scientific, 2004)
This invaluable book represents a substantial body of work describing the theory of the optical properties of thin island films and rough surfaces. In both cases the feature sizes are small compared to the wavelength of light. The approach is extremely rigorous and theoretically very thorough. The reflection, transmission and absorption of light are described. Computer programs that provide exact solutions for theoretical properties of thin island films have recently become available, and this makes the book of great practical use.